Effect of laser phototherapy on algiic perception, fear of movement and quality of life of subjects with myofascial pain associated with fibromyalgia (Research, Society and Development, 2022)
The study evaluated the effectiveness of laser phototherapy on the myofascial trigger point of the trapezius muscle in fibromyalgic patients. 25 individuals were diagnosed with myofascial pain and fibromyalgia and divided into groups: Laser (n=8), Laser + medication (n=10) and Medication (n=7) and treated for 5 weeks. The variables measured were: 1) Pain intensity using the Visual Analogue Scale (VAS); 2) Pressure pain threshold (PPT) using a pressure algometer; 3) General pain status using the Rolland-Morris Questionnaire (QIRM); 4) Fear of moving according to the Tampa Scale for Kinesiophobia (ETC) and 5) Assessment of the impact of Fibromyalgia on quality of life (QIF). The data obtained were analyzed using two-way analysis of variance (ANOVA) for repeated measures, followed by Tukey's post-test, when appropriate. For cases where the interaction between the factors (Treatment and Time) was significant, one-way repeated measures ANOVA was conducted for each treatment group. All tests were two-tailed and p